Laporan Perbandingan Kinerja - Angelina Wijaya Tan; Nathalie Elshaday Betrix Ambouw; Shirky Kharisma Fitri Hasnita; Nurul Laily Oktaviani; Putri Rima Nirwana (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
This study aims to compare the performance of PT Metro Healthcare Indonesia, PT Kalbe Farma Tbk, PT Indocement Tunggal Prakarsa Tbk, PT Siloam International Hospitals Tbk, and PT Hetzer Medical Indonesia Tbk. The focus of the research is the analysis of financial and operational performance to provide an in-depth understanding of the companies' competitiveness and efficiency within their respective sectors. The study employs a quantitative method with a descriptive-comparative approach. Secondary data were collected from the annual financial reports of each company over a specific period. The analysis was conducted using key financial ratios such as Return on Equity (ROE), Debt to Equity Ratio (DER), and Current Ratio (CR). Additionally, an operational performance trend analysis was performed to understand the comparative effectiveness of the companies in resource management. The results of the analysis indicate significant differences in financial performance between companies operating in the healthcare sector (PT Metro Healthcare Indonesia, PT Kalbe Farma Tbk, PT Siloam International Hospitals Tbk, and PT Hetzer Medical Indonesia Tbk) and those in the building materials sector (PT Indocement Tunggal Prakarsa Tbk). Companies in the healthcare sector tend to have higher profitability ratios compared to those in the building materials sector, although there are variations in debt and asset management efficiency. These performance differences can be attributed to underlying industry factors such as market demand, levels of innovation, and government policies. Companies in the healthcare sector benefit from growth driven by increasing public demand for healthcare services. In contrast, the building materials sector is more vulnerable to economic fluctuations and infrastructure investments. This study concludes that industry sectors and business models have a significant impact on companies' financial performance. Healthcare sector companies demonstrate more stable and promising performance compared to the building materials sector. This study is expected to provide insights for investors in selecting suitable investment portfolios.